Solitary primary peritoneal carcinoma arising from the omentum - Yi-Jou Tai; Ming-Chieh Lin; Chin-Jui Wu; Chi-An Chen; Wen-Fang Cheng (Elsevier, 2014)
Objective: To report a case of isolated omental peritoneal carcinoma without peritoneal carcinomatosis. Case report: A 60-year-old female with abdominal distention was found to have a pelvic mass. Under the impression of ovarian cancer, laparotomy was performed only to show one isolated mass over omentum. Serial examination and pathology study including immunochemical staining indicated primary peritoneal serous carcinoma. Conclusion: Isolated omental peritoneal carcinoma without peritoneal carcinomatosis and ascites is rare, and whether this represented a unique entity with different chemotherapy response and treatment outcome from the disseminated form of primary peritoneal carcinoma needs to be reviewed in the future.